Thomas Chatterton, the Marvelous Boy : With "The Exhibition," a Personal Satire - Ellinger, Esther Parker (University of Pennsylvania Press, 1930)
A psychological analysis of Chatterton's contradictory mental characteristics, with the first complete publication of his violent verses against the citizens of Bristol.
Keywords: Chatterton, Thomas, -- 1752-1770.; Chatterton, Thomas, -- 1752-1770; Literary forgeries and mystifications -- History -- 18th century.; Poets, English -- 18th century -- Biography.; Faux et supercheries littéraires -- Histoire -- 18e siècle.; Poètes anglais -- 18e siècle -- Biographies.; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Literary forgeries and mystifications; Poets, English; 1700-1799; Cultural Studies.; Literature.; Biographies; History